Przydatność erodowanych gleb porolnych jako siedliska leśnego w oparciu o Indeks Trofizmu Gleb Leśnych (ITLG) = Suitability of eroded fallows as forest habitat on base of Forest Soil Trophism Index (FSTI) - Chudecka, Justyna; Tomaszewicz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Authors in this work determined, on base of Forest Soil Trophism Index (FSTI), the suitability of eroded fallows as forest habitat. On base of soil quality classification these soils independently from localization in relief are habitat of mixed coniferous. According FSTI the soils from summit and slope belong to habitat of mixed forests and forests but soils of delluvial zone belong to habitat of forests.
Keywords: zalesianie; grunty porolne; gleby erodowane i namywane; uziarnienie; właściwości chemiczne; indeks trofizmu gleb leśnych (ITGL); forestation; fallows; eroded and delluvial soils; soil texture; chemical properties; Forest Soil Trophism Index (FSTI)